1998
DOI: 10.1074/jbc.273.6.3778
|View full text |Cite
|
Sign up to set email alerts
|

Two Caenorhabditis elegans Actin Depolymerizing Factor/Cofilin Proteins, Encoded by the unc-60 Gene, Differentially Regulate Actin Filament Dynamics

Abstract: The Caenorhabditis elegans unc-60 gene encodes two actin depolymerizing factor/cofilin proteins which are implicated in the regulation of actin filament assembly in body wall muscle. We examined the interaction of recombinant UNC-60A and B proteins with actin and found that they differentially regulate actin filament dynamics. Co-pelleting assays with F-actin showed that UNC-60A depolymerized but did not remain bound to F-actin, whereas UNC-60B bound to but did not depolymerize F-actin. In the pH range of 6.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
125
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 91 publications
(127 citation statements)
references
References 38 publications
2
125
0
Order By: Relevance
“…However, ADF is more sensitive to changes in pH than cofilin 61 . In addition, in the mouse and C. elegans, the non-muscle isoforms cofilin 1 and ADF are more efficient at depolymerizing F-actin in vitro than the muscle isoform of cofilin 62,63 . These findings suggest that specific cofilin isoforms may be crucial to the changes in cell shape and migration that occur during different stages of embryonic development and morphogenesis.…”
Section: Box 2 Linking Cofilin To Drosophila Melanogaster Morphogenesismentioning
confidence: 98%
“…However, ADF is more sensitive to changes in pH than cofilin 61 . In addition, in the mouse and C. elegans, the non-muscle isoforms cofilin 1 and ADF are more efficient at depolymerizing F-actin in vitro than the muscle isoform of cofilin 62,63 . These findings suggest that specific cofilin isoforms may be crucial to the changes in cell shape and migration that occur during different stages of embryonic development and morphogenesis.…”
Section: Box 2 Linking Cofilin To Drosophila Melanogaster Morphogenesismentioning
confidence: 98%
“…UNC-60B is an I-band protein, which controls the turnover of actin filaments by accelerating the rate of depolymerization at the pointed ends and by severing actin filaments 22,14 . Fluorescence microscopy of contracting body wall muscles of C. elegans revealed that GFP-UNC-60B was indeed abnormally accumulated along I-bands in the contracted state in the dbn-1 (ok925) mutant and in dbn-1 (RNAi) worms compared with the regular pattern in wild-type worms ( Fig.…”
Section: Nature Communications | Doimentioning
confidence: 99%
“…The bestdescribed protein of the first class in C. elegans is the ADF/ cofilin homologue UNC-60B. Inside the sarcomere, this protein is localized to the I-band and enhances actin-filament turnover by accelerating the rate of depolymerization at the pointed ends and by severing filaments 22,14 . Mutations in the unc-60B gene result in the formation of highly disorganized sarcomeres and the appearance of large aggregates of actin at the lateral ends of bodywall muscle cells 23 .…”
mentioning
confidence: 99%
“…The forms differ in their filament severing and depolymerizing abilities and tissue locations. UNC-60A is required for proper early development and UNC-60B for muscle sarcomere structure (Ono and Benian, 1998;Ono et al, 1999Ono et al, , 2003Ono, 2003;Yamashiro et al, 2005). The C-terminal portion of UNC-60B is critical for its interactions with filamentous actin .…”
Section: Thin Filamentmentioning
confidence: 99%